Teacher Strategy in Parents Organization Class (POC) Activities to Form Collaboration Between Teachers and Parents of Students at MIN 2 Malang - Febrianti, Aristhalia Hevi; Rahmawati, Iin Nur Indah; Derajat, Lingga Saniman; Aprilia, Chofifah Dwi; Romadhon, Muhammad Syahru; Musyarofah, Lindarty Dian (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3138, 2024)
This study aims to explain the strategies that can be applied by teachers in teaching activities. Parents Organization Class( POC) to form better collaboration between teachers and parents of students at MIN 2 Malang, especially in supporting school programs that can support the student learning process.The type of research used is a qualitative research type with a case study method. This method was chosen because it can provide a deep understanding of the interaction and collaboration between teachers and parents of students, as well as the dynamics that occur in Parents Organization Class (POC) activities. Data collection was carried out by field research. Data sourced from interviews, observation and documentation. Data analysis techniques by means of researchers being directly involved in organization activities to observe interactions between teachers and parents. The results of observations, interviews, and analysis of research documents show that teacher strategies in POC activities greatly influence collaboration between teachers and parents. Active involvement of parents in discussions and positive feedback indicate that they feel they have an important role in their children's education. In addition, open and transparent communication between teachers and parents is key to building trust and cooperation. Thus, organization activities not only serve as an information forum, but also as a platform for building stronger relationships between schools and families.